2019
DOI: 10.3390/en12030371
|View full text |Cite
|
Sign up to set email alerts
|

6.78-MHz, 50-W Wireless Power Supply Over a 60-cm Distance Using a GaN-Based Full-Bridge Inverter

Abstract: An inductive wireless power transfer system is proposed as a power supply for an on-line monitoring system for an overhead catenary. Because of the high voltage (25 kVrms) applied to the catenary, galvanic isolation was required to supply power to the attached monitoring system. The proposed wireless power system was able to transmit 50 W over a distance of 60 cm at 6.78 MHz. Design methodologies for the transmitter and the receiver coils, 6.78-MHz GaN-based full-bridge inverter, and rectifier are proposed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 25 publications
(33 reference statements)
0
2
0
Order By: Relevance
“…On the other hand, Lee examined in his study in 2019 that WPT systems can be adapted in different sizes in places where it is difficult to reach. Also, he transferred 47 W power with 52% efficiency with WPT at a distance of 60 cm which is the approach distance of the high voltage lines (Lee et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Lee examined in his study in 2019 that WPT systems can be adapted in different sizes in places where it is difficult to reach. Also, he transferred 47 W power with 52% efficiency with WPT at a distance of 60 cm which is the approach distance of the high voltage lines (Lee et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, they have been used in various applications, such as battery charging [2], drones [3], LED lighting [4], and biomedicine [5]. Many studies have demonstrated the excellent performance of class-E power amplifiers [6,7], particularly when gallium nitride high electron mobility transistors (GaN HEMTs) are used [7][8][9][10][11]. GaN HEMTs provide high efficiency and performance due to their exceptional characteristics, such as low gate charge loss [7] and gate-source capacitance, which almost produce an ideal ZVS [8,9].…”
Section: Introductionmentioning
confidence: 99%